INTEGRASI KURIKULUM PESANTREN DAN SEKOLAH UMUM DALAM PEMBENTUKAN KARAKTER MODERN ISLAMI - Masruhan Zakariya, Ahmad; Afiful Ikhwan; Bambang Harmanto; Muhammad Abdul Rahim (LPPM STAI Muhammadiyah Probolinggo, 2023)
As a result of advancements in telecommunications, transportation, and technology, Indonesian education faces four challenges related to globalisation in the areas of culture, morals, and ethics. The alternative is to create an integrated school that merges traditional and Islamic boarding schools, focusing on academic, religious, and character characteristics with solid cultural reinforcement. This research analyses the concepts, strategies, and implications of integrating Islamic boarding school and public school curricula in forming modern Islamic characters at the Zumrotus Salamah Tawangsari Islamic Boarding School, Tulungagung. This study uses a qualitative approach, a case study type; data collection techniques using in-depth interviews with the Chair of the Foundation, the Headmaster, a sample of 5 teachers, and a sample of 3 students (santri), participant observation during the learning process and documentation of the curriculum structure of the Zumrotus Salamah Islamic Boarding School, participant observation and documentation; data analysis techniques: data presentation, data reduction, and concluding; data checking was carried out through diligent observation and triangulation tests. Research Results: (1) The concept of integrating the curriculum of Islamic boarding schools and public schools in the formation of modern Islamic character by correlating the core (government) curriculum with the pesantren curriculum whose primary reference is from the book of aqidatul awwam and the involvement of education experts and senior humanists; (2) Integration strategy by instilling tafaqquh fid dien (taqwa that does not lose cultural identity), periodic evaluations according to stakeholder needs, integrating a curriculum that has a modern Islamic character, especially in extracurricular activities; (3) The implication of integration is that there is a diametrical relationship between morals and culture, which affects the style of speech and manners of students, school formal wear uses traditional Javanese clothing, extracurricular activities with old Javanese games such as enggrang, dakonan, coblak-coblak suweng, etc. which instill the values of tolerance, togetherness, growing mutual trust (honesty), justice and patience according to QS. Al-Maidah: 8.